Amnesia of the Operating Room in the B-Unaware and BAG-RECALL Clinical Trials. (April 2016) - Chen, Yulong; Cai, Alice; Fritz, Bradley A.; Dexter, Franklin; Pryor, Kane O.; Jacobsohn, Eric; Glick, David B.; Willingham, Mark D.; Escallier, Krisztina E.; Winter, Anke C.; Avidan, Michael S.
Abstract : BACKGROUND: Patient memories of the operating room (OR) may serve as the informational basis for assessing satisfaction with individual anesthesiologists. Furthermore, the provision of clinically important information may assume that perioperative memories are retained. Studies assessing the extent of perioperative amnesia and factors associated with perioperative amnesia are sparse. Therefore, we assessed patient amnesia of the OR and of the preoperative holding area in hospitals where midazolam is typically administered in the preoperative holding area and evaluated whether midazolam dose administered in the preoperative holding area and patient age were associated with amnesia of the OR before induction of anesthesia. METHODS: This was a retrospective study among 7750 adult patients who had general anesthesia and participated in the B-Unaware and Bispectral Index or Anesthetic Gas to Reduce Explicit Recall (BAG-RECALL) clinical trials. The last location the patient remembered before induction of anesthesia and the first location they remembered after induction of anesthesia were determined through a modified Brice questionnaire administered over the phone 30 days postoperatively. Regarding the preoperative period, patients were excluded if their last memory was unclear with respect to location before induction of anesthesia or if they were recruited at Winnipeg, where midazolam was typically first administered in the OR. Midazolam dose (mg/kg) administered in the preoperative holding area was divided into quartiles. Poisson regression models were used to calculate age- and multivariable-adjusted odds ratios (95% confidence intervals [CIs]) for the association between midazolam dose and amnesia of the OR before induction of anesthesia. RESULTS: Of the 5339 patients included, 59.5% (95% CI, 58.2–60.9) of patients had amnesia of the OR before induction of anesthesia. In addition, 44.1% (95% CI, 42.8–45.7) last remembered the preoperative holding area, and 15.4% (95% CI, 14.4–16.4) only had preoperative memories before the holding area. The percentages of patients with amnesia of the OR before induction of anesthesia differed according to age groups: 50.7% (95% CI, 47.7%–53.7%) in patients aged 18 to 47 years versus 70.0% (95% CI, 67.0%–72.9%) in patients aged 73 to 99 years. Patients in the highest midazolam quartile had an adjusted prevalence ratio of 1.31 (95% CI, 1.22–1.42) for amnesia of the OR compared with those who did not receive midazolam. CONCLUSIONS: In hospitals where patients typically receive midazolam in the preoperative holding area, the majority of patients do not remember the OR, and a clinically relevant number of patients does not remember the preoperative holding area. If additional studies produce results indicating that a substantial proportion of patients has amnesia of the anesthesiologist, these findings would argue against the validity of assessing patient satisfaction with individual anesthesiologists providing exclusively OR care in such hospitals. Furthermore, if additional studies yield findings suggesting patient amnesia of the preoperative holding area, these results would suggest reconsideration of providing clinically important information only in the preoperative holding area. Older age and midazolam-induced anterograde amnesia are probably associated with impaired perioperative memories.